Determinants of talent retention in Mexico: leadership, climate and happiness management - Salazar-Altamirano, Mario-Alberto; Galván-Vela, Esthela; Ravina-Ripoll, Rafael; Martínez-Arvizu, Orlando-Josué (ANDULI, Revista Andaluza de Ciencias Sociales, 2025)
Understanding what organisational factors most influence staff turnover remains a challenge in human talent management. This study addresses this issue by examining how transformational leadership, work climate, and happiness management interact to explain turnover intention. A sample of 414 workers from various industries in Mexico was surveyed, and data were analysed using structural equation modelling. The findings show that transformational leadership significantly influences work climate and happiness management. However, as expected given the mediating structure of the model, there is no direct effect between transformational leadership and turnover intention. Instead, work climate and happiness management act as mediators, with happiness management playing a direct and significant role in reducing turnover intention. These results reveal complex interdependencies and underscore the importance of promoting leadership styles and organisational strategies that strengthen happiness management to enhance talent retention and organizational sustainability.